Rising Hindutva’s Impact on Strategic Stability in South Asia - Dr Summar Iqbal; Muhammad Kumail Mehdi (CISS Insight Journal, 2023)
The rise of Hindutva has become internalized in India, making it an aggressive state, and has exacerbated South Asia’s strategic instability. Religious extremism is now a significant issue of discussion in Indian political circles. The Bharatiya Janata Party not only represents its ideals but also promotes the Hindutva mindset. If Hindutva continues to be the guiding principle for shaping Indian decision-making processes, the Indian leadership is likely to become more inflexible in dealing with other states, more so with its neighbors – the relationship with Pakistan is a case in point. Moreover, India has been rapidly increasing its defense spending for the last decade and a half. With the additional funds available for defense, India has imported advanced and sophisticated weapon systems and made huge investments in the domestic production of defense equipment. South Asian strategic stability has been further undermined by BJP’s defining credo of Hindutva which led to the enactment of the Indian Citizenship Amendment Act, the rise of fundamentalist Yogi Adityanath, and an increase in tensions with Pakistan. This paper elaborates on how the rise of Hindutva is inimical to strategic stability in South Asia.